Craving changes in first 14 days of addiction treatment: an outcome predictor of 5 years substance use status? - Emmanuelle Baillet; Marc Auriacombe; Cassandre Romao; Hélène Garnier; Christophe Gauld; Chloé Vacher; Joël Swendsen; Mélina Fatseas; Fuschia Serre (Translational Psychiatry)
Abstract Addiction is considered a chronic disorder that requires long-term treatment. Early identification of predictors of outcome may enable better and early adjustment of treatment. Daily fluctuations of craving have been shown to predict substance use within hours, making it a major target for treatment. The objective of this study was to examine whether trajectory and temporal dynamics of craving, at the initiation of outpatient addiction treatment, were associated to long-term substance use outcome. An Ecological Momentary Assessment study collected craving intensity changes and substance use during the first 14-days of treatment, followed by prospective regular follow-ups for 5 years or more to assess long-term outcome. Analysis investigated whether individual differences in craving trajectory (linear trend) and dynamics (inertia, variability and instability) predicted 5+ years follow-up outcome: substance use (1 day or more of primary substance use/past 30 days) versus abstinence. Thirty-nine participants were enrolled in addiction clinic in Bordeaux, France. Results showed that substance use at 5+ years was significantly associated with slower decrease of craving intensity (p < 0.001), and a lower craving inertia (p = 0.038), i.e. tendency to persist from one moment to the other, compared to abstinence status. Conversely, craving intensity was not found associated with substance use/abstinence at follow-up. Results suggest that a slower decrease in craving at treatment initiation could express a greater resistance to treatment. This resistance may have many mechanisms, among which a persistent reactivity to cues – as suggested by lower inertia – that could constitute a vulnerability to use and a valuable indicator of long-term outcomes.